Minimal effects of visual memory training on auditory performance of adult cochlear implant users - Oba, Sandra I.; Galvin III, John J.; Fu, Qian-Jie (Journal of rehabilitation research and development, 2013)
Auditory training has been shown to significantly improve cochlear implant (CI) users' speech and music perception. However, it is unclear whether posttraining gains in performance were due to improved auditory perception or to generally improved attention, memory, and/or cognitive processing. In this study, speech and music perception, as well as auditory and visual memory, were assessed in 10 CI users before, during, and after training with a nonauditory task. A visual digit span (VDS) task was used for training, in which subjects recalled sequences of digits presented visually. After the VDS training, VDS performance significantly improved. However, there were no significant improvements for most auditory outcome measures (auditory digit span, phoneme recognition, sentence recognition in noise, digit recognition in noise), except for small (but significant) improvements in vocal emotion recognition and melodic contour identification. Posttraining gains were much smaller with the nonauditory VDS training than observed in previous auditory training studies with CI users. The results suggest that posttraining gains observed in previous studies were not solely attributable to improved attention or memory and were more likely due to improved auditory perception. The results also suggest that CI users may require targeted auditory training to improve speech and music perception.